PENGARUH FANATISME ORGANISASI TERHADAP KEBERHASILAN BELAJAR MAHASISWA PAI IAIN CURUP - Hendra Harmi (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2022)
This research is a survey research and field research with a combined technique. Sequential model design and sequential explanation method. All respondents are active activists, including HMI, PMII, IMM, and KAMMI. Non-probability sampling-purposive sampling is the sampling approach used. This research is a hybrid of survey research and field research. Sequential model design and sequential explaining technique This research is a hybrid of survey research and field research. Sequential model design and techniques explain sequentially. The sample size is 65 PAI IAIN Curup students. This study aims to determine the level of success of student learning achievement. The results of this study indicate that some Islamic student activists prefer to be fanatical to their organizations, both internal and external fanaticism, and organizational fanaticism has a beneficial influence on the performance of PAI students at IAIN Curup.